Ethical Perspectives on Synodality - Agius, Emmanuel (Asian Horizons, 2025)
This paper investigates the ethical dimensions of synodality, a perspective rarely addressed in current scholarship yet essential to understanding the Church’s present trajectory. Drawing on the Preparatory Document, the Vademecum, the Working Document for the Continental Stage Enlarge the Space of Your Tent, the International Theological Commission’s 2018 text, and the teachings of Pope Francis, the study situates synodality within the broader horizon of moral theology. It argues that synodality is not simply a procedural or structural innovation but a journey of moral and spiritual conversion, rooted in the cultivation of virtues, renewal of ecclesial structures, and formation of Christian character. Framed by three guiding questions— What kind of Church are we now? What kind of Church do we want to become? How do we get there?—this research highlights synodality as an ethical path toward communion, participation, and mission, requiring transformation at personal, communal, and institutional levels.